The Effect of Social Responsibility on the Relationship between Investment, Financing and Performance of Companies admitted to the Tehran Stock Exchange - Afshin Nokhbeh Fallah; Farhad Fazilat (پژوهش‌های تجربی حسابداری, 2025)
Nowadays, the goal of organizations is not limited to maximizing profits and welfare, but it is also necessary to pay special attention to their surroundings. The appropriate response of organizations to this issue is to pay attention to the legal, ethical and environmental requirements that are referred to as Corporate Social Responsibilities The purpose of this study is to investigate the effect of corporate social responsibility(CSR) on the relationship between investment and performance as well as external financing and performance. For this purpose, 127 firms listed in the stock exchange were selected as the research sample and the effect of social responsibility on the relationship between the mentioned variables in the two periods of 1395 -1402 was examined. Regression analysis based on panel data was used to test the hypotheses The results of the research show that corporate social responsibility has a moderating effect on the relationship between investment and performance. However, the hypothesis that the moderating effect of social responsibility on the relationship between investment and performance is less in companies with slack resources was not confirmed. According to another result of the research, social responsibility has a moderating effect on the relationship between external financing and financial performance; therefore, it can be concluded that in socially responsible companies, investments are more dependent on cash generated within the company than on external financing. This research will help managers understand the impact of social responsibility policies in achieving better financial performance in the long term. Managers are advised to pay special attention to social responsibility reporting, which is a bridge between the enterprises and multiple stakeholders.